The top 100 most cited articles on axon regeneration from 2003 to 2023: a bibliometric analysis - Saijilafu,; Ye, Ling-Chen; Zhang, Jing-Yu; Xu, Ren-Jie (Frontiers in Neuroscience, 2024)
Objective In this study, we used a bibliometric and visual analysis to evaluate the characteristics of the 100 most cited articles on axon regeneration. Methods The 100 most cited papers on axon regeneration published between 2003 and 2023 were identified by searching the Web of Science Core Collection database. The extracted data included the title, author, keywords, journal, publication year, country, and institution. A bibliometric analysis was subsequently undertaken. Results The examined set of 100 papers collectively accumulated a total of 39,548 citations. The number of citations for each of the top 100 articles ranged from 215 to 1,604, with a median value of 326. The author with the most contributions to this collection was He, Zhigang, having authored eight papers. Most articles originated in the United States (n = 72), while Harvard University was the institution with the most cited manuscripts (n = 19). Keyword analysis unveiled several research hotspots, such as chondroitin sulfate proteoglycan, alternative activation, exosome, Schwann cells, axonal protein synthesis, electrical stimulation, therapeutic factors, and remyelination. Examination of keywords in the articles indicated that the most recent prominent keyword was “local delivery.” Conclusion This study offers bibliometric insights into axon regeneration, underscoring that the United States is a prominent leader in this field. Our analysis highlights the growing relevance of local delivery systems in axon regeneration. Although these systems have shown promise in preclinical models, challenges associated with long-term optimization, agent selection, and clinical translation remain. Nevertheless, the continued development of local delivery technologies represents a promising pathway for achieving axon regeneration; however, additional research is essential to fully realize their potential and thereby enhance patient outcomes.